PENERAPAN UJI T-BERPASANGAN UNTUK MELIHAT PENGARUH PEMBINAAN SISWA DALAM MENGHADAPI PERSIAPAN LOMBA OLIMPIADE MATEMATIKA - Ulfasari Rafflesia; Pepi Novianti; Dian Agustina; Idhia Sriliana (DHARMA RAFLESIA, 2017)
ABSTRACTBengkulu is an active participant in the National Science Olympic competition in junior level. But the achievement of Bengkulu’s students is not prominent, especially in the fieldof Mathematics. Until now Bengkulu has never been quite encouraging achievement in theOSN. Department of Mathematics University of Bengkulu has a human resource that ispromising, the competent faculty who can nurture, guide, and prepare students of SMPNegeri 2 Bengkulu to compete in the OSN. Therefore, students of SMP 2 Bengkulu will becoached to understand, analyze and answer the questions, so that they know the mathOlympic the strategy and the ways that fast in answering the Olympics questions correctly,so they will be a champion at the provincial and national competition. After coaching isdone, it can be concluded that this activity has not been a significant influence. However,development activities that have been implemented are able to provide the knowledge andinsight to junior high school students about the material and questions in math Olympic.Keywords: SMP Negeri 2, Math Olympic, paired T-test